The use of active game approach in teaching children at the Manila Youth Reception Center. - Buenavista, Pedro M. ([Quezon City] : University of the Philippines, 1973)
The search for the best method of teaching children with behavior problems have always been the concern of parents, social workers, special education teachers and many others who believe that through proper guidance and the use of the right teaching approach, these children would find education a growing experience. Among the recent innovations in education, the use of active games as a medium in teaching these children offers great promise. Besides the pleasurable experiences derived from the active game approach, children are offered significant outlet for vigorous physical activity and mental creativity. Included in this paper are some recommended active games in teaching reading arithmetic. While this study made use of the children at the Manila Youth Reception Center, whose interests formed the basis for recommending the active game approach for their learning, it is hoped that this paper will also benefit other children in the said institution: be they in special education classes or in the regular classrooms.
In partial fulfillment of the requirements for the Degree Master of Arts in Teaching Special Education
A seminar paper presented to the faculty of the Graduate School of Education, University of the Philippines
Thesis (M.A.) - University of the Philippines
Keywords: Delinquents -- Education; Manila Youth Reception Center